Analysis of a data set in a multi-criteria assessment of variants of a building development - Marlena Anna Jurczak; Jolanta Harasymiuk; Elżbieta Szafranko (Archives of Civil Engineering)
One of the most important things to do at the stage of preparing an investment process in the construction business is to develop a few possible solutions and then to choose the variant which best fulfils the expectations of various groups of stakeholders. Making a decision about which variant to select depends on how it satisfies a number of criteria, which in turn reflect the requirements set for the planned investment. The process analysing variant solutions employs multi-criteria analysis methods. In order to make analyses and to identify the importance of measurable and non-measurable criteria, surveys and interviews are carried out to acquire the information on the role of the previously defined criteria. Opinions given by experts tend to be divergent due to differences in education, professional background as well as various professional and private experiences. This article reviews data processing methods, and discusses an example of a procedure, which is part of a more extensive analysis of the route of a planned road. The case presented in this paper focuses on the evaluation of five criteria from the category ‘impact on the natural environment’, which are significant in such development projects. The calculations involved in this assessment proved to be time- and labour-consuming, while raising a number of doubts concerning the stage of data aggregation. Hence, the objective of this study has been to develop a method that will enable more efficient data processing while taking into account all assessments.